Outcomes of Waterbirth in a US Hospital‐Based Midwifery Practice: A Retrospective Cohort Study of Water Immersion During Labor and Birth. (6th September 2019) - Neiman, Emily; Austin, Elizabeth; Tan, Alai; Anderson, Cindy M.; Chipps, Esther
Abstract : Introduction: Although the safety of water immersion during labor is largely supported by evidence from research, the risks to women and neonates during waterbirth are not well established. The purpose of this study was to generate evidence regarding maternal and neonatal outcomes related to water immersion in labor and during birth. Methods: A retrospective cohort study included a convenience sample of women receiving prenatal care at a nurse‐midwifery practice. Participants were categorized into 3 groups: 1) waterbirth, 2) water labor, or 3) neither. Participant characteristics, maternal outcomes, and newborn outcomes were collected at time of birth and health record abstraction. At the 6‐week postpartum visit, another maternal outcome, satisfaction with birth, was measured using the Care in Obstetrics: Measure for Testing Satisfaction (COMFORTS) scale. Analysis included effect size, descriptive statistics (sample characteristics), and maternal and neonatal group differences (analysis of variance and chi‐square) with a significance level of P < .05. Results: Women in the waterbirth (n = 58), water labor (n = 61), and neither (n = 111) groups were primarily white, married, and college educated and did not differ by age or education. Women in the waterbirth group were more likely to be multiparous. Nulliparous women who had a waterbirth had a significantly shorter second stage of labor than nulliparous women who did not have a waterbirth ( P = .03). The most commonly cited reasons for discontinuation of hydrotherapy were maternal choice (42.6%) and need for pain medication (29.5%). Significantly more women in the waterbirth group experienced a postpartum hemorrhage, compared with water labor or neither (n = 5, n = 3, n = 1, respectively; P = .045); there was no difference in related clinical measures. Neonatal outcomes were not significantly different. Maternal satisfaction was high across all groups. Discussion: The results of this study suggest that waterbirth, attended by qualified intrapartum care providers in hospital settings in the United States, is a reasonable option for low‐risk women and their neonates.